New Discoveries in Smaller Antiquities and a Unique Portrait Sculpture from Medieval Bengal Duars - Sarker, Archishman (Religions of South Asia, 2022)
This paper studies some unpublished smaller antiquities in stone, terracotta and copper alloys, made between the tenth and the thirteenth centuries, from the region of Bengal Duars, housed at the Archaeological Survey of India site-shed at Gosanimari, Coochbehar, and at the Akshaya Kumar Maitreya Heritage Museum of North Bengal University. While some of them represent a style stemming from the late-Pala period, others present a unique and region-specific artistic idiom. Most were found accidentally and collected by local historians and antiquarians, and were donated to the AKMHM; others were found at three prominent sites: Bhitargarh, Ghoshpukur and Gosanimari. These sites, situated in an ecologically fragile region, have a rich history of different kinds of local worship which were attuned to the environment and nature; the art of the region also reflects an interaction with the larger milieu of Indic and Himalayan religious practices. This article further investigates a large stone sculpture housed at the AKMHM, also from the Bengal Duars, and questions its labelling as a Danapati.